Origem ectópica da artéria coronária direita: a propósito de um caso clínico - Costa, S (2010)
Coronary artery anomalies can occur in isolation or in association with other congenital heart defects. Clinical presentation ranges from asymptomatic forms to sudden cardiac death. The authors report a case of anomalous origin of the right coronary artery from the left sinus of Valsalva, diagnosed with multidetector computed tomography coronary angiography.